Public Policy on Science and Technology to promote business management in rural areas - Guzmán Achallma, Carlos Luis (2022)
The main objective of the research was to determine if the National Policy that promotes the development of Science, Technology and Innovation (PNDCTI) influences the business management of the alpaca fiber producers in San Mateo. The methodology used was a non-experimental, cross-sectional and correlational design. Likewise, after carrying out the investigation and subsequent act of statistical processing, it was possible to verify that PNDCTI influences the business management of alpaca fiber producers in the place of study, finally a proposal for a solution to the problem is developed as a contribution of the investigation. , which highlights the opportunity for improvement to guide research in science and technology with the business sector in order to give them sustainability; It should be noted that the research on the matter was the product and thanks to the financing through the stimuli provided by the National Council of Science, Technology and Technological Innovation -Concytec.